2007
DOI: 10.1634/stemcells.2007-0299
|View full text |Cite
|
Sign up to set email alerts
|

A High Concentration of Epidermal Growth Factor Increases the Growth and Survival of Neurogenic Radial Glial Cells Within Human Neurosphere Cultures

Abstract: Human neural progenitor cells (hNPC) isolated from the fetal cortex can be expanded as aggregates of cells termed neurospheres. Traditional methods have used 20 ng/ml epidermal growth factor (EGF) to drive the proliferation of these cells. Here, we show that 100 ng/ml EGF can significantly increase growth rates of hNPC at later passages. This was through increased survival of dividing cells rather than increased proliferation and associated with prolonged activation of ErbB2 and phosphorylated Akt. High EGF al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…There is evidence that biochemical factors can promote stem cell differentiation into various stages and types of neural cells 3,4 such as neural progenitor cells (NPCs), 5,6 mature neurons, 7 dopaminergic neurons, 8 and glial cells. 9 However, the exact roles of various growth factors in neural differentiation remain to be elucidated to improve the efficiency of cell differentiation. Among the studies on neural differentiation, basic fibroblast growth factor (bFGF) is known to be an important growth factor that increases neurite extensions in PC12 cells, 10 increases neurogenesis from human NPCs, 11 and stimulates neural cell differentiation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that biochemical factors can promote stem cell differentiation into various stages and types of neural cells 3,4 such as neural progenitor cells (NPCs), 5,6 mature neurons, 7 dopaminergic neurons, 8 and glial cells. 9 However, the exact roles of various growth factors in neural differentiation remain to be elucidated to improve the efficiency of cell differentiation. Among the studies on neural differentiation, basic fibroblast growth factor (bFGF) is known to be an important growth factor that increases neurite extensions in PC12 cells, 10 increases neurogenesis from human NPCs, 11 and stimulates neural cell differentiation.…”
mentioning
confidence: 99%
“…4 Early studies in rat 13 and mouse 14 models have shown that sustained EGF treatment increases NPC differentiation into the glial lineage, and more recent studies with human NPCs show an increase in radial glial differentiation. 9 In this study, we directly compared the effects of bFGF and EGF on gene expression of neural markers during human ESC differentiation, and determined their effects on axon growth.…”
mentioning
confidence: 99%
“…This possibility was also confirmed in another paper using culture with a high concentration of EGF, which also increased neural production in hNPCs [59]. Traditional methods have used 20 ng ml −1 EGF to drive the proliferation of neurospheres.…”
Section: Increased Neurogenic ''Radial Glial''-like Cells Within Humamentioning
confidence: 71%
“…We recently found that there are different types of cells in proliferating hNPCs by using double labeling with GFAP and nestin following acute plating [50,59]. We found that in undifferentiated progenitor cells there are three different morphologies in hNPCs: (i) small and flat, (ii) elongated and radial, or (iii) large and flat cells (Figure 19.4e) [59].…”
Section: Increased Neurogenic ''Radial Glial''-like Cells Within Humamentioning
confidence: 75%
See 1 more Smart Citation